Rapid estimation of gamma number of viscose by UV Spectrophotometry - Lanieri, Diana Beatriz (2014)
Viscose process is the most important method for industrial cellulose dissolution. The degree of substitution (DS) is an important parameter in cellulose derivatives, and it is usually expressed as a gamma number (γ No.). In this work, viscose was prepared from eucalyptus and cotton linter dissolving pulps. Two methods were used for by-product separation: coagulation method (CM, reference) and ion exchange method (IEM). Similar γ Nos. were obtained with both methods for viscoses from cotton linters. The molar absorptivity of cellulose xanthate at 303 nm (e303nm) was determined by, firstly, measuring the absorbance of different purified viscoses and, subsequently, drawing a linear regression with the values obtained. The purification efficacy of IEM was analyzed from the UV peaks obtained in the range of 220-380 nm of the original and purified viscoses. The disappearance of the absorption of the main byproduct, sodium trithiocarbonate, was observed. Finally, with the e303nm mentioned above and the absorbance measurement of the purified viscoses, their γ Nos. were determined using a spectrophotometric method (SM). This would indicate that UV spectrophotometry could be used to estimate this parameter in a quick and easy way, which is decisive for the use of viscose in regenerated cellulose products.